2018
DOI: 10.5089/9781484376362.001
|View full text |Cite
|
Sign up to set email alerts
|

Financial Access Under the Microscope

Abstract: We examine the impact of a large-scale microcredit expansion program on financial access and the transition of previously unbanked borrowers to commercial banks. Using administrative micro-data covering the universe of loans to individuals from a developing country, we show that the program significantly increased access to credit, particularly in less developed areas. This effect is driven by the newly setup credit cooperatives (U-SACCOs), which grant loans to previously unbanked individuals. A sizable share … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 31 publications
(46 reference statements)
0
2
0
Order By: Relevance
“…De Janvry, McIntosh, and Sadoulet (2019) document that the use of credit bureau services by a microfinance lender in Guatemala improved screening of new clients, increased the size of loans, but also led to an increase of expulsion of existing clients. Agarwal et al (2018) showed that a microcredit program coupled with a well-functioning credit bureau in Rwanda improved individuals' access to commercial bank loans at favorable conditions.…”
Section: Policies To Enhance Households' Financial Inclusionmentioning
confidence: 99%
“…De Janvry, McIntosh, and Sadoulet (2019) document that the use of credit bureau services by a microfinance lender in Guatemala improved screening of new clients, increased the size of loans, but also led to an increase of expulsion of existing clients. Agarwal et al (2018) showed that a microcredit program coupled with a well-functioning credit bureau in Rwanda improved individuals' access to commercial bank loans at favorable conditions.…”
Section: Policies To Enhance Households' Financial Inclusionmentioning
confidence: 99%
“…It is therefore not surprising that government interventions aimed at increasing access to cheaper credit have not resulted in lower use of informal finance (Gine, 2011). Nonetheless, Agarwal et al (2018) document how government-sponsored credit cooperatives in Tanzania, together with a functioning credit bureau, helped increase formal credit, though they also find that more formal financial institutions tend to cream-skim borrowers.…”
Section: Introductionmentioning
confidence: 96%